Verification of velocity‐resistivity relationships derived from structural joint inversion with borehole data. Issue 14 (23rd July 2013) - Moorkamp, M.; Roberts, A. W.; Jegen, M.; Heincke, B.; Hobbs, R. W.
Abstract : [1] We present results of three‐dimensional joint inversion of seismic, magnetotelluric, and gravity data over a marine salt dome. Such structures are difficult to image with a single method, and our results demonstrate how combining different techniques can yield improved results. More importantly, we examine the reliability of velocity‐conductivity relationships derived from structure‐coupled joint inversion approaches. Comparison with a seismic reflection section shows that our models match the upper limit of the salt. Furthermore, velocity and resistivity logs from a borehole drilled into the salt dome's flank match, within error, those recovered by the inversion. The good match suggests that the difference in length scale does not have a significant effect in this case. This provides a strong incentive to incorporate borehole data into the joint inversion in the future and substantiates approaches that use the relationships derived from joint inversion models for lithological classification. Key Points: First test of velocity‐conductivity relationship derived from joint inversion First 3D joint inversion of MT, seismic and gravity data